Frequency of early post operative complications of modified radical mastectomy within period of four weeks - Melwani, Rekha; Malik, Sadaf Jabeen; Shakeel, Sobohi; Zafar, Shahid; Khoso, Muhammad Yousif; Ali, Syed Naqeeb (International Journal of Research in Medical Sciences, 2020)
Background: Most of the complications are developed after modified radical mastectomy in breast cancer patients, hence to avoid and reduces the postoperative complications, this study is performed to identify the frequency of early post-operative complications of modified Radical Mastectomy within the period of four weeks. Methods: Cross-sectional case series using non-probability convenient sampling technique was conducted in surgical unit I of Tertiary care hospital, for 1 year from 15 January 2018 to 14 January 2019. 89 patients FNAC proved breast cancer were included, patients that received neoadjuvant chemo or radiotherapy or with inflammatory breast cancer, metastasis and with co-morbid were excluded. After taking consent patients were operated by senior consultant. Follow up was taken daily 7th post-operative day and then followed in OPD on weekly basis fourth week and final outcome was noted. SPSS version 23 was used for data analysis. Quantitative data was reported as frequency in percentages. Results: Total 31 patients developed complications during the study, accounts 34% of total patients. The most common complication was breast seroma in 12(13.48%) of cases with an increased risk in cases of age >50 yr, size of tumor >8 cm, weight >70 kg and increased number of lymph nodes [3 or above] palpable after wards hematoma in 6(6.74%), lymphedema in 5(5.62%), wound infection 4(4.49%) and shoulder dysfunction in 4(4.49%) patients, no patient was found scar hypertrophy. Conclusions: Seroma formation, hematoma were found most common early complications after modified radical mastectomy, lymphedema, wound infection and shoulder dysfunction were observed in small number of patients.